Islamic and Dutch Schools in Jambi During Colonial Era - Ema Pratama Agustiningsih; Singgih Tri Sulistyono; Dhanang Respati Puguh (Diponegoro University, 2021)
This article discusses the development of Islamic and Dutch schools in Jambi, 1901-1942. This study adopted a historical method, including, heuristics, criticism, interpretation, and historiography. Jambi was one of Dutch territories. All aspects of life were governed by Dutch rule, including education. Education in Jambi had been developed since the entry of Islam at the end of the 11th century, long before the Dutch education system was introduced in the 20th century. Since the ethical policy had been enacted, all colonies were obliged to implement the Dutch or European education system and open Dutch schools, including in Jambi. Dutch schools for indigenous people were established in 1914 under Hollands Inlandsche School (HIS). These schools trained indigenous or local people in the language, which distinguished it from the students of Europeesche Lagere School (ELS) which had existed since 1903. In its development there were several Dutch schools such as De Tweede Klasse School, Volkschool, Vervolgschool, Special Education for the Chinese, vocational schools or Ambacht School Voor Inlanders (ASVI). Therefore, the implementation of the Dutch education system in Jambi was particularly well-developed, but on another hand, it could not replace the traditional education system which had been previously and informally implemented by the community in langgar (small mosques) and madrasas. These traditional schools were formalized and fulfilled with facilities, in this regard classrooms and halls